The Minnowbrook Conference III, 2008 and the state of public administration - Chakrabarty, Bidyut (2012)
Public administration has become a complex area of human endeavour simply because of equally complex socio-economic circumstances in which it is rooted as a practice. In order to meet the 'new' demands the discipline needs to shake off its ethnocentric character. By implication public administration has to remain inter-disciplinary and appreciate cross-disciplinary borrowing unlike in its earlier incarnations when it drew heavily on grand theories and remained 'inflexible'. The growing acceptance of governance to mean public administration also confirms that it no longer remains 'boundary conscious' and the issues that emerged at third Minnoebrook Conference are reflective of a growing openness to new ideas, coupled with enduring issues that span the decades. - Reproduced.
Keywords: Public administration